Robust Dual-Loop Control With Disturbance Observer for DT-PMSM Driven Steer-by-Wire Systems - Kunpeng Jiang; Yousheng Yang (IEEE Access)
The Steer-by-Wire (SBW) system, driven by a Dual Three-Phase Permanent Magnet Synchronous Motor (DT-PMSM), has attracted significant attention due to its advantages. However, parameter uncertainties and external disturbances pose challenges to precise steering control. To achieve accurate, fast, and robust control, this paper proposes a dual-loop control structure. The outer loop uses a Proportional-Integral (PI) controller to manage the steering angle, while the inner loop employs a Sliding Mode Controller (SMC) to regulate speed. The paper first introduces the structure of the DT-PMSM-driven SBW system and compares two existing methods for rack force estimation: one based on the steering system dynamics and the other based on vehicle dynamics. Through experiments under various input conditions, the strengths and weaknesses of each method are analyzed. Based on these analyses, a fuzzy logic-based data fusion method is proposed to combine the results of the two estimation methods, dynamically adjusting the weights using fuzzy logic to significantly improve the accuracy of the rack force estimation. Furthermore, a disturbance observer is introduced into the dual-loop control structure, resulting in a novel active tracking controller. The proposed control algorithm leverages the coordination between the inner and outer loops to effectively address system nonlinearities and uncertainties. The performance of the controller is validated through software-in-the-loop simulations and test bench experiments. The results show that the proposed controller achieves high accuracy in rack force estimation, with the overall error controlled within 800N across all operating conditions. Additionally, the controller demonstrates superior tracking control performance. Specifically, in ramp tests, the ATC controller reduces IAE by 64.17% and 87.85% compared to PID and SMC, RMSE by 65.87% and 72.08%, and MAE by 64.44% and 87.97%, respectively.